2004
DOI: 10.1002/sia.1986
|View full text |Cite
|
Sign up to set email alerts
|

SEM and RBS characterization of a cobalt‐based conversion coating process on AA2024‐T3 and AA7075‐T6

Abstract: Samples of aluminium alloys AA2024-T3 and AA7075-T6 were treated with a chromate-based deoxidizer, then conversion coated with a commercial cobalt-based solution and finally sealed with a commercial vanadate-based product. The alloy specimens were examined using scanning electron microscopy, transmission electron microscopy and Rutherford backscattering spectroscopy. The thickness of the cobalt-based conversion coating increased rapidly up to 5 min of immersion but more slowly for longer times. Sealing resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…[27][28][29] Chromate conversion films are usually prepared by chemical treatment and have a low thickness. A number of compounds of several transition metals in a high oxidation state have been used for chemical conversion coatings, such as titanium, 38 vanadium, 39 zirconium and niobium, 40 manganese, 41,42 cobalt, 43 molybdenum, 44 tungsten and silicon, 45 cerium, 40,[46][47][48][49] and other rare earth metals. To increase the sustainability of the protective effect, chromate anticorrosive pigments such as CaCrO 4 , SrCrO 4 , or BaCrO 4 should be incorporated into the more extended primer layer.…”
Section: Methods For Combating Corrosion: Short Overviewmentioning
confidence: 99%
“…[27][28][29] Chromate conversion films are usually prepared by chemical treatment and have a low thickness. A number of compounds of several transition metals in a high oxidation state have been used for chemical conversion coatings, such as titanium, 38 vanadium, 39 zirconium and niobium, 40 manganese, 41,42 cobalt, 43 molybdenum, 44 tungsten and silicon, 45 cerium, 40,[46][47][48][49] and other rare earth metals. To increase the sustainability of the protective effect, chromate anticorrosive pigments such as CaCrO 4 , SrCrO 4 , or BaCrO 4 should be incorporated into the more extended primer layer.…”
Section: Methods For Combating Corrosion: Short Overviewmentioning
confidence: 99%
“…7.7(a) shows a porous cobalt oxide coating on both an intermetallic particle and the matrix on AA2024-T3. 152 This process was developed by Schreiver. 153 Fig.…”
Section: Boehmite Formation In Solutions Containing Rare Earthsmentioning
confidence: 99%
“…[18] As for the reported CCPs, one of the most remarkable processes is cobaltate CCP, and the main reasons are as follows: Co is an essential trace element for the human body and an essential component of vitamin B12; the equilibrium potential of Co 3+ /Co 2+ (+1.82 V) ion pair is higher than that of Cr 6+ /Cr 3+ (+1.56 V), which means that the corrosion resistance of Co conversion coating (CoCC) is better than that of Cr conversion coating (CrCC) from the perspective of thermodynamics. Nevertheless, several studies have reported that CoCC has an open porous rigid structure, [19][20][21] and the corrosive medium is easy to penetrate, causing the reduction of its corrosion resistance. Consequently, the construction of chromium-free CoCC without honeycomb structure is one of the most promising processes to replace CrCC.…”
Section: Introductionmentioning
confidence: 99%